2009
DOI: 10.1177/19714009090220s110
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of White Matter Hyperintensities in Alzheimer's Disease: Post-Mortem Quantitative MRI and Neuropathology

Abstract: White matter hyperintensities (WMH) are frequently seen onT 2 -weighted MRI scans of elderly subjects with and without Alzheimer's disease. WMH are only weakly and inconsistently associated with cognitive decline, which may be explained by heterogeneity of the underlying neuropathological substrates. The use of quantitative MRI could increase specificity for these neuropathological changes. We assessed whether post-mortem quantitative MRI is able to reflect differences in neuropathological correlates of WMH in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 40 publications
(66 reference statements)
2
33
0
1
Order By: Relevance
“…4 Remyelination or other evidence of resolution of pathology was not observed in that study, but it would certainly be important to scrutinize those findings in independent studies on different samples. Combined with a moderate activation of microglia, these observations are certainly compatible with secondary (wallerian) degeneration, similar to what has been reported in white matter hyperintensities in Alzheimer disease by Gouw et al 27 If DAWM indeed represents secondary axonal degeneration, studying DAWM changes in vivo will be of paramount importance for understanding and monitoring the disease process.…”
Section: Discussionsupporting
confidence: 64%
“…4 Remyelination or other evidence of resolution of pathology was not observed in that study, but it would certainly be important to scrutinize those findings in independent studies on different samples. Combined with a moderate activation of microglia, these observations are certainly compatible with secondary (wallerian) degeneration, similar to what has been reported in white matter hyperintensities in Alzheimer disease by Gouw et al 27 If DAWM indeed represents secondary axonal degeneration, studying DAWM changes in vivo will be of paramount importance for understanding and monitoring the disease process.…”
Section: Discussionsupporting
confidence: 64%
“…They concluded that both techniques are sufficiently suited to detect microstructural tissue alterations at least in the white matter of the murine brain. Postmortem histological analyses assessing myelin content, axonal density, and gliosis revealed similar correlations in brains of patients with Alzheimer's disease [29] or multiple sclerosis [71][72][73].…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 72%
“…Table 4 describes the results of DTI and MTI in various settings and disease entities. Animal models and postmortem studies indicate that increased fractional anisotropy and mean diffusivity derived from DTI and magnetization transfer ratio from MTI correlate with axonal loss, demyelination and dentritic injury [29,36,70,76]. A recent study in hypoperfused mice is of particular interest as it examined the complementary value of DTI and MTI measures for delineation of white matter damage [36].…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 99%
“…6 Ex vivo MRI proves to be a valuable tool in determining MR markers in brain diseases with multiple small focal abnormalities such as vascular lesions and demyelination, providing whole-brain coverage and targeted sampling for histopathologic examination. [14][15][16] A recent study suggested that prolonged storage (46 years) of formalin-fixed tissue results in subtle histology artifacts, which sometimes on ex vivo MRI is indistinguishable from genuine brain pathology. 17 In our case, we have solely used postmortem brain tissue that has been stored for no longer than 15 months, therefore we assume our samples are not susceptible for mentioned alterations in the tissue and on the corresponding MR images.…”
Section: Discussionmentioning
confidence: 99%